THE SELF DENIAL OF ‘LENA’ AS THE MAIN CHARACTER IN THE FILM ENTITLED ‘COLONIA’ BY FLORIAN GALLENBERGER AND TORSTEN WENZEL - Nisa Nur Aini; Ch. Evy Tri Widyahening (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
The study aims to analyze the self-denial of the main character in the film entitled ‘Colonia’ by Florian Gallenberger and Torsten Wenzel. The researcher used qualitative descriptive method. The data collected by researcher were reading the script of film, watching the film, and note taking record all data film. The researcher used the validity triangulation data and triangulation theory to check the validation. The result of the research showed that form of selfdenial were refusing to talk about the problem, looking for ways to justify their behaviour, lying or ignoring one’s own feelings (manipulative), blaming others for the problems experienced, avoiding thinking about the problem which had the impacts of Lena and another characters namely, lying, breaking the rules, feeling guilty, manipulative, wounding, death. The role of supporting characters in influencing the Lena’s inner conflict could be found in the film Colonia, such as Daniel, Pius, and Gisela.   Key Words: Self-denial, Colonia Film, Lena, Impacts